A snapshot of the 2020 conception of anatomic liver resections and their applicability on minimally invasive liver surgery. A preparatory survey for the Expert Consensus Meeting on Precision Anatomy for Minimally Invasive HBP Surgery. (21st April 2021) - Ciria, Ruben; Berardi, Giammauro; Nishino, Hitoe; Chan, Albert C.Y.; Chanwat, Rawisak; Chen, Kuo‐Hsin; Chen, Yajin; Cheung, Tan To; Fuks, David; Geller, David A.; Iwashita, Yukio; Liu, Rong; et al.
Abstract: Background: The main aim of this survey was to analyze how liver surgeons perform liver resections and to define their conception of anatomic procedures within the incorporation of minimally invasive liver surgery (MILS). Methods: The survey was distributed among liver surgeons. It mainly focused on personal experience on open and MILS, methods and landmarks, and experience on anatomic resections and Glissonean approach. Results: A total of 445 valid answers from 54 countries was obtained. Surgeons performing MILS mainly have below 10 years of experience (81.8% of responders) and one third has never done complex MILS. New techniques, including indocyanine green demarcation are marginally used (<25%). More than 60% of surgeons do not make a full exposure of hepatic veins during MILS, mainly due to the risk of injury or not considering it to be of utility. Although 88% of responders agreed with the concept of anatomic resection as the "resection along the border/watersheds of each order division identified by the portal vein flow", only 55% of surgeons have ever performed MILS Glissonean approaches. Conclusions: Liver anatomy is not a static concept. Anatomic resections need training and precision. Standardization of complex anatomic resections by a minimally invasive approach should be encouraged. Abstract : Highlight Ciria and colleagues conducted a survey to analyze how liver surgeons perform liver resections and to define their conception of anatomic procedures related to minimally invasive liver surgery (MILS). A total of 445 valid answers from 54 countries offer a snapshot of how liver surgery is performed around the world.